2015
DOI: 10.1109/jssc.2015.2471847
|View full text |Cite
|
Sign up to set email alerts
|

A SiGe Terahertz Heterodyne Imaging Transmitter With 3.3 mW Radiated Power and Fully-Integrated Phase-Locked Loop

Abstract: A high-power 320 GHz transmitter using 130 nm SiGe BiCMOS technology ( 220/280 GHz) is reported. This transmitter consists of a 4 × 4 array of radiators based on coupled harmonic oscillators. By incorporating a signal filter structure called return-path gap coupler into a differential self-feeding oscillator, the proposed 320 GHz radiator simultaneously maximizes the fundamental oscillation power, harmonic generation, as well as on-chip radiation. To facilitate the TX-RX synchronization of a future terahertz (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(30 citation statements)
references
References 36 publications
(65 reference statements)
0
24
0
Order By: Relevance
“…A OPT and Φ OPT are the optimum voltage gain and phase shift for the two-port at f max . Equations (8) and (9) are derived assuming no clipping to the power rails occurs inside the circuit. If clipping happens, another set of equations apply for A OPT ; Φ OPT remains the same [8,9].…”
Section: Power Gain Maximization For a Given Active Devicementioning
confidence: 99%
See 2 more Smart Citations
“…A OPT and Φ OPT are the optimum voltage gain and phase shift for the two-port at f max . Equations (8) and (9) are derived assuming no clipping to the power rails occurs inside the circuit. If clipping happens, another set of equations apply for A OPT ; Φ OPT remains the same [8,9].…”
Section: Power Gain Maximization For a Given Active Devicementioning
confidence: 99%
“…Since the above derivation is restricted to f max , it would be interesting to observe the possible deviations of Eqs. (8) and (9) with respect to the two-port's voltage gain and phase shift under biconjugate matching when operating at frequency below f max . A SiGe HBT transistor is used as an example.…”
Section: Power Gain Maximization For a Given Active Devicementioning
confidence: 99%
See 1 more Smart Citation
“…This frequency is nearly twice of that of the implemented SiGe:C-based CMOS THz transmitters in 2015 that could emit frequencies up to 0.32 THz. 137,138 TeraFETs have the potential of being realized by CMOS technology and thus provide a promising building block for implementation of compact economical THz cameras. It is observed that such devices show good potential for edge detection and enhanced spatial resolution for THz imaging applications.…”
Section: Antenna-coupled Field-effect Transistors For the Plasmonic Dmentioning
confidence: 99%
“…One approach to overcome this hurdle has been to apply a variety of on-chip multiplication [18] and free-space power combining techniques [19]. However, so far, mainly because of the inadequate f T and f MAX of the CMOS and SiGe BiCMOS technologies employed, the reported output power, power added efficiency, and phase noise at frequencies >200 GHz have remained lower than 5 dBm, 0.5%, and −84 dBc/Hz at 1-MHz offset, respectively.…”
Section: N Recent Years Several Foundries Have Reported Sigementioning
confidence: 99%